2012
DOI: 10.1111/j.1468-2354.2012.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy Rules and the Sustainability of Public Debt in Europe*

Abstract: The sustainability of public debt is interpreted as the result of the interaction of fiscal policy with the economic environment, and not as a statistical concept as in most of the recent literature. If debt is not to explode over time, policymakers have to respond to the changing conditions in the macroeconomic environment. This article defines the conditions that will ensure compliance of fiscal policy with the intertemporal budget constraint in the context of Europe's fiscal policy rules. The empirical part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 21 publications
(30 reference statements)
0
37
0
3
Order By: Relevance
“…This implies that in Sri Lanka the tax rate does not respond significantly to either debt or deficit alone. Further, the rule where the primary balance reacts to debt and deficit proposed by Collignon (2012) does not seem to be suitable for Sri Lanka, as reflected by the statistically insignificant debt coefficients. The simple rule where the primary balance responds only to the overall deficit works fairly well except that it is not a widely used rule and, more importantly, it is not very informative.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that in Sri Lanka the tax rate does not respond significantly to either debt or deficit alone. Further, the rule where the primary balance reacts to debt and deficit proposed by Collignon (2012) does not seem to be suitable for Sri Lanka, as reflected by the statistically insignificant debt coefficients. The simple rule where the primary balance responds only to the overall deficit works fairly well except that it is not a widely used rule and, more importantly, it is not very informative.…”
Section: Resultsmentioning
confidence: 99%
“…In normal times this is a fairly soft requirement. Collignon (2012) has shown that this condition has been fulfilled over the last 20 years. Although beta is rarely significant in Europe, alpha varies in the range of 16% (Belgium) to 73% (Germany), with Greece (35%) and Italy (23%) in the middle.…”
Section: Debt Sustainabilitymentioning
confidence: 89%
“…How can we judge that this condition is fulfilled? It turns out that there is a very simple condition that makes public debt sustainable (Collignon 2012). The condition is derived from a system of two differential equations, one describing the intertemporal budget constraint (1), the other describing the fiscal policy reaction function stipulated by the EDP and the SGP (2).…”
Section: Debt Sustainabilitymentioning
confidence: 99%
“…Given our parameter assumptions (namely,   1), and the linearity of the aggregate production function in the private capital stock, the crowding-out effect dominates the crowding-in effect and the net impact on growth of higher debt is (all things equal, specifically for   given) always negative. 12 In the standard definition of fiscal (or debt) sustainability, a fiscal policy is said to be sustainable if the present value of future primary surpluses equals the current level of debt (see, for instance, Collignon (2012)). Put differently, the budget must be balanced in present value terms to rule out Ponzi games.…”
mentioning
confidence: 99%